Navigating Economic Growth: The Role of Twin Deficits in APEC Member Economies - Resti Amalina; Dedy Yuliawan; Nurbetty Herlina S (International Journal of Economics, Business and Innovation Research, 2024)
This research examines how the twin deficits (budget deficit and trade balance) influence economic growth in APEC members. Economic growth serves in place of the variable that is dependent, with the budget deficit and balance of trade as the variables that are independent. The 15 APEC member economies that are covered by the panel data was employed in this inquiry for the years 2018–2021. Throughout the investigation, panel data regression was adopted and the Common Effect Model (CEM) was decided on. As shown by its findings, the budget deficit significantly and favorably affects economic growth, whereas the trade balance has no appreciable effect. Both balance of trade and budget shortfall have a notable effect on growth of the economy concurrently.